Predicting Treatment Response of Neoadjuvant Chemoradiotherapy in Locally Advanced Rectal Cancer Using Amide Proton Transfer MRI Combined With Diffusion-Weighted Imaging - Chen, Weicui; Mao, Liting; Li, Ling; Wei, Qiurong; Hu, Shaowei; Ye, Yongsong; Feng, Jieping; Liu, Bo; Liu, Xian (Frontiers in Oncology, 2021)
Objective: To evaluate amide proton weighted (APTw) MRI combined with diffusion-weighted imaging (DWI) in predicting neoadjuvant chemoradiotherapy (NCRT) response in patients with locally advanced rectal cancer (LARC). Methods: 42 patients with LARC were enrolled in this prospective study. MR examination including APTw MRI and DWI was performed before and after NCRT. APTw SI, ADC value, tumor size, CEA level before and after NCRT were assessed. The difference of the above parameters between before and after NCRT was calculated. The tumor regression grading (TRG) was assessed by American Joint Committee on Cancer’s Cancer Staging Manual AJCC 8th score. The Shapiro-Wilk test, paired t-test and Wilcoxon Signed Ranks test, two-sample t-test, Mann-Whitney U test and multivariate analysis were used for statistical analysis. Results: Of the 42 patients, 16 had good responses (TRG 0-1), 26 had poor responses (TR2-3). After NCRT, All the rectal tumors demonstrated decrease APT values, increased ADC values, reduced tumor volumes and CEA levels (all p < 0.001). Good responders demonstrated higher pre-APT value, higher Δ APT value, and lower pre- ADC value than poor responders. Pre-APT combined with pre-ADC achieved the best diagnostic performance, with AUC of 0.889 (sensitivity of 84.62%, specificity of 87.50%, p < 0.001) in predicting good response to NCRT. Conclusion: The combination of APTw and DWI may serve as a noninvasive biomarker for evaluating and identifying response to NCRT in LARC patients.